GENDER DISPARITY TOWARDS STUDENTS ENROLLMENT IN TECHNICAL EDUCATION IN RIVERS STATE: CAUSES, EFFECTS AND STRATEGIES - Dokubo, Isaac Nwojiewho; Deebom, Mtormabari Tambari (International Journal of Research -GRANTHAALAYAH, 2017)
This study examined the gender disparity towards students’ enrollment in technical education in Rivers State. A sample of 403 students (362 Male and 41 Female) was selected through simple random sampling technique from Rivers State University (RIVSU) and Ignatius Ajuru University of Education (IAUOE), Port Harcourt from the Department of Technical Education. Three research questions were posed to guide the study and two Null hypotheses were formulated and tested at 0.05 level of significant. Structured questionnaire was used to collect data. A reliability coefficient of 0.83 was established through Cronbach Alpha using test-retest method. Data were analyzed using mean and standard deviation for research questions and hypotheses were tested using the independent sample t-test. The study revealed amongst others that poverty, preference of male child, cultural and religious beliefs were causes of female folks low enrollment into technical education programmes in Rivers State. Based on the findings of the study, it was recommended amongst others that; allowances, scholarships, employment opportunities should be given to female students in order to enhance their enrolments into technical education programmmes in Rivers State.